2004
DOI: 10.1242/jcs.01058
|View full text |Cite
|
Sign up to set email alerts
|

Levels of human Fis1 at the mitochondrial outer membrane regulate mitochondrial morphology

Abstract: Mitochondria undergo balanced fission and fusion events that enable their appropriate networking within the cell. In yeast, three factors have been identified that co-ordinate fission events at the mitochondrial outer membrane. Fis1p acts as the outer membrane receptor for recruitment of the dynamin member, Dnm1p and the WD40-repeat-containing protein Mdv1p. In mammals, the Dnm1p counterpart Drp1 has been characterized, but other components have not. Here, we report the characterization of human Fis1 (hFis1). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
272
3
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(301 citation statements)
references
References 40 publications
23
272
3
3
Order By: Relevance
“…results are also consistent with a previous report showing that overexpression of yeast Fis1 in yeast cells displayed no enhanced mitochondrial fragmentation (Mozdy et al 2000). However, overexpression of human Fis1 in mammalian cells was reported to induce mitochondrial fragmentation and cytochrome c release (James et al 2003), though others have described alternative human Fis1-induced morphologies in mammalian cells (Yoon et al 2003;Stojanovski et al 2004). …”
Section: Mitochondrial Fission and Cell Death Genes And Development 2791supporting
confidence: 92%
See 1 more Smart Citation
“…results are also consistent with a previous report showing that overexpression of yeast Fis1 in yeast cells displayed no enhanced mitochondrial fragmentation (Mozdy et al 2000). However, overexpression of human Fis1 in mammalian cells was reported to induce mitochondrial fragmentation and cytochrome c release (James et al 2003), though others have described alternative human Fis1-induced morphologies in mammalian cells (Yoon et al 2003;Stojanovski et al 2004). …”
Section: Mitochondrial Fission and Cell Death Genes And Development 2791supporting
confidence: 92%
“…Fis1 of Saccharomyces cerevisiae is an 18-kDa protein that is anchored to the outer mitochondrial membrane by a C-terminal hydrophobic-basic domain characteristic of Bcl-2, Tom 5, and other proteins targeted to the outer mitochondrial membrane (Mozdy et al 2000;Kaufmann et al 2003). Consistent with its role in yeast, depletion of endogenous human Fis1 decreases mitochondrial fission (James et al 2003;Yoon et al 2003;Stojanovski et al 2004).…”
mentioning
confidence: 92%
“…2 Previous experiments have demonstrated that mitochondrial fragmentation cannot be caused by overexpression of any mitochondrial protein. 17,18 Nevertheless, production of high nonphysiological levels of G72 may be a confounding factor in the interpretation of the results outlined above. Because we could not detect and, therefore, monitor the levels of endogenous G72 protein in six tested human cell lines, we have been unable to complement our overexpression analysis with siRNA-based loss-offunction approaches.…”
Section: Increase In G72 Levels Results In Mitochondrial Fragmentatiomentioning
confidence: 99%
“…Mitochondrial fusion mixes mitochondria contents, thus enabling protein complementation (Detmer and Chan, 2007). The disruption of fusion leads to the fragmentation of the mitochondrial tubular network (Griparic et al, 2004), while abnormal fission causes elongated and interconnected tubules (Stojanovski et al, 2004).…”
Section: Mitochondria Fission and Fusionmentioning
confidence: 99%